Cortactin in Epithelial–Mesenchymal Transition - Ji, Rong; Zhu, Xiao-Juan; Wang, Zhi-Rong; Huang, Li-Qiang (Frontiers in Cell and Developmental Biology, 2020)
Cortactin, as a member of the ABP family, plays an important role in cell movement involving the cytoskeleton, cell movement mediated by it can induce EMT. The study found that cortactin participates in tumor proliferation, migration and invasion and other related disease processes by its binding to different proteins and participation in different pathways and mechanisms to induce occurrence. Therefore, this article reviews the correlation between cortactin and the actin cytoskeleton and EMT and discusses its clinical significance in tumor therapy.